Language Learning Strategies Used by Accounting Students - Estisari, Kristina; Sinaga, Imelda (Universitas Teknokrat Indonesia, 2024)
English is an international language that must be mastered by accounting students in Indonesia because they will need English to communicate in their future work. However, English is not their first language. English is their foreign language. They face a lot of difficulties in learning English. While they are learning accounting as their major, they also have to learn English which is related to their field of study. Therefore, effective English learning strategies will help accounting students to achieve their learning targets efficiently. This research aims to determine the English learning strategies used by accounting students. The type of research used is descriptive quantitative research. Data were collected using a questionnaire and analyzed by using a Likert scale and processed by using SPSS 23. The sample used in this research was 56 respondents who were 4th and 6th semester of accounting students at a STIE in Lampung, who had studied English on campus for about 2 years. Based on their level of English ability, students are divided into 3 levels, namely Beginner, Intermediate, and Advance levels. The results of the research show that Accounting students who were at the Beginner level used the Metacognitive strategies the most, students at the Intermediate level used the Memory strategies the most, and students at the Advanced level used the Metacognitive strategies the most. Overall, Accounting students in this research used the Memory strategy the most with the highest mean score of 3.70. The second used strategy is Metacognitive strategy with a Mean score of 3.67. The third is Social strategy with a Mean score of 3.53. The fourth is Cognitive strategy with a Mean score of 3.41. The fifth is Compensation strategy with a Mean score of 3.37. While, the least used strategy by participants in learning English is Affective strategy, with the lowest Mean score of 3.33.